Analisis Margin dan Keuntungan Pemasaran Daging Ayam Broiler di Pasar Swalayan Kota Manado - Nangoy, Stanley (JBE (Journal of Business and Economics); Volume 2 No.1, 2003 JBE UNKLAB, 2003)
Each trading activity, particularly broiler locally and regionally, seemed that traders held important role for market activity which happened on the area. The matter was done, due to they expected she great advantage which could be as their man income for full filled the family need. The problem on the research, was hour much marketing. Margin and  profit did they achieve and did marketing-benefit significantly affect to margin which received by traders. Aim of the research was to investigate how much marketing-margin and profit achieved by, and did marketed price by broiler affect significantly to margin which received by trades in Manado city. Analysis method was application on the research, was descriptive analysis method which guided by data performing an tables, more that that by empirical method which guided by a set of statistical analysis as test-tool. Value of marketed margin which achieved in broiler trading was affected by benefit-value. These could was explained by coefficient of determinant (R 2 ) summed 0,077. It meant that 77%  of marketing-margin was affected by number of benefit from traders on supermarket’s in Manado city.